Constrained entrepreneurship in UK agriculture: A Weberian analysis. (October 2022) - Gittins, Peter; McElwee, Gerard; Lever, John
Abstract: This conceptual paper draws on Max Weber's Iron Cage metaphor to explore its value in understanding how farmers are responding to the institutional contexts that influence and constrain entrepreneurial activities. We create Ideal Types of farmers, farm businesses and farm business strategies to provide a nuanced understanding into the heterogeneous ways Upland farmers are navigating and responding to ever-shifting Constrained Institutional Contexts (CIC's). We examine Weber's original cage metaphor, and draw on its limitations by framing it alternatively to provide a unique lens to examine the UK farming context. We add clarity into how farmers are responding to the challenges arising from the contexts within which they operate, providing a strong theoretical underpinning that can be used by other scholars to examine constrained rural entrepreneurship. Highlights: Ideal type of Farmers. Weberian Analysis. Uncertainty in the UK farming sector. UK Agricultural policy will have a dramatic effect on the UK farm sector.